The Clinicoetiopathological study of Madhumeha (Type-2 Diabetes Mellitus) with special reference to Deha Prakriti - Kumar, Yogendra; Pandey, Anurag; S.Byadgi , Parameswarappa (International Journal of Psychosocial Rehabilitation, 2024)
Prameha is a syndrome manifest by involving complex interaction between doshas anddushyas in srotas (multiple systems) especially mutravaha srotas leading to development ofseveral distinct types and are caused by a complex interaction of genetics (sahaja, kulaja,jataja, adibala pravritta, anushangi), life style factors (Apathyanimittaja) and environmentalfactors1,2, & 3.